PROFIL MANAJEMEN WAKTU SISWA KELAS IX SMPN 1 LELES - Fauzianty Putri Salvatianty; Samsudin, Asep; Pahlevi, Reza (IKIP Siliwangi, 2024)
This study intends to look at the time management profile of grade IX students at SMPN 1 Leles. Reviewed in terms of aspects of time management, gender, and class grades so that it is obtained to determine the profile of time management in students. Survey-based quantitative research focuses on this research. This is a population of 401 students at SMPN 1 Leles. The sampling technique is selected based on the random sampling technique. Based on the results of data acquisition, it shows that most students have time management skills that are being seen from the average value of class results.The average score of female students of 98.60 is categorized as medium, while in men a score of 98.79 is obtained. However, based on the average results, the higher scores are in male learners. Based on aspects, time management has 5 aspects, in the aspect of having an average goal of results in 401 learners, which is 43, in the aspect of having an average planning of results 12, in the aspect of being able to utilize the average time of results 16, in the aspect of prioritizing the average time of results 17, and the last aspect is participating in activities that are liked on average results 11. It can be seen that the highest average gain is the aspect of having planning.